Chest Girth, Body Weight, and Body Condition Score of Female Swamp Buffaloes at Different Altitudes in West Sumatra, Indonesia - Reswati; Salam Ningsih Aritonang (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
The purpose of this study is to analyze the variation of chest girth, body weight, and body condition score (BCS) of female swamp buffaloes raised in areas with different altitudes in West Sumatra. Factors such as temperature humidity index (THI) and forage quality were also analyzed as supporting factors. This study was conducted using a survey method at three regions: lowland (Lubuk Basung Regency, Agam Regency, 26–46 m above sea level), moderate land (Akabiluru Regency, Lima Puluh Kota Regency, 570–632 m above sea level), and highland (Matur Regency, Agam Regency, 851–1190 m above sea level). The study sample comprises 104 adult, non-pregnant female buffaloes, selected using purposive sampling. The results showed that chest girth, body weight, and BCS differed significantly among the three regions (p<0.05). Water buffalo reared in moderate land performed the highest chest girth (187.45 cm), body weight (522.6 kg), and BCS (3.16), followed by buffalo reared in highland and lowland areas. Better body performance in the moderate land was supported by more comfortable environmental conditions and relatively higher forage quality in that area. In conclusion, environmental altitude influences variations in chest girth, body weight, and BCS in female swamp buffalo, with moderate and highland areas providing the most favorable conditions for optimal body performance.